COASTAL COMMUNITY PARTICIPATION IN KELURAHAN SUKOLILO, BULAK, BASED ON LOCAL ECONOMY (DIMENSI: Journal of Architecture and Built Environment, 2017)
Kelurahan Sukolilo, Bulak Settlement is an area of fishermen settlement with great potential of resources such as fish and sea cucumber. Kelurahan Sukolilo also well known as Prominent Kampung in fish processed products. Despite having a great potential in marine resources, most of the fishermen still live in a low environmental and economic condition. Theres hould be effective environmental management in coastal area so the fiherman vulnerability can be reduced through a criteria of developing coastal area that is able to accomodate the fisherman economic activities. The researcher will apply community based development in developing coastal area criteria.. In this case community-based development approach needs to be developed in the management of coastal areas, especially for the improvement of the environmental quality. This is because the coastal characteristic and resources are very complex and diverse, so in the coastal area management should involve the local community directly. Community based management shows the importance of community participation in development planning and implementation. This research was in form of qualitative research, data sources obtained by primary and secondary data. Primary data were collected through observations, visual documentations and interview with the fishermen and fish processors. Secondary data were obtained from literature and theory. Research results showed that  level of community participation that need to be done in the development process using active participatory. Active participatory should be done through partnership and delegated power level to accomodate fishermen and fish processors activities and support sustainable environment. Co-working space for inhabitants is needed  to accomodate community activities related to water and odor and drying process and to create area to socialize